(untitled) (Global Journal of Medical Research, 2020)
Introduction: With the development of the availability of genetic research, a multiplex approach to determining the pharmacotherapy tactics has become possible, taking into account the individual characteristics of the patient. Nevertheless, the modern tactics of pharmacotherapy #x201C;to failure#x201D; has been adopted, which over time leads to the intensification of therapy. A personalized approach to the pharmacotherapy of type 2 diabetes mellitus by determining the genotype of endothelial synthase of nitric oxide will predict the effectiveness of metformin monotherapy in the debut of the disease and reduce the risk of decompensation and complications with long-term type 2 diabetes mellitus. The aim of the study was to monitor the effectiveness of metformin pharmacotherapy for long-term type 2 DM, depending on the patient#x2019;s genotype.